Correction: Neurological diagnoses in hospitalized COVID-19 patients associated with adverse outcomes: A multinational cohort study. - Meghan R Hutch; Jiyeon Son; Trang T Le; Chuan Hong; Xuan Wang; Zahra Shakeri Hossein Abad; Michele Morris; Alba Gutiérrez-Sacristán; Jeffrey G Klann; Anastasia Spiridou; Ashley Batugo; Riccardo Bellazzi; et al. (PLOS Digital Health)
[This corrects the article DOI: 10.1371/journal.pdig.0000484.].